2020
DOI: 10.1136/bmjopen-2019-034682
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial consequences of false positives in the Danish Lung Cancer CT Screening Trial: a nested matched cohort study

Abstract: ObjectivesLung cancer CT screening can reduce lung cancer mortality, but high false-positive rates may cause adverse psychosocial consequences. The aim was to analyse the psychosocial consequences of false-positive lung cancer CT screening using the lung cancer screening-specific questionnaire, Consequences of Screening in Lung Cancer (COS-LC).Design and settingThis study was a matched cohort study, nested in the randomised Danish Lung Cancer Screening Trial (DLCST).ParticipantsOur study included all 130 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 35 publications
3
27
2
1
Order By: Relevance
“…Screening, in its own right, introduces the risk of negative psychosocial consequences which might be long-term. However, in the previously mentioned matched cohort study we found short-term, but no evidence supporting long-term psychosocial consequences [13]. We argue that certain long-term consequences may have been overlooked, or that the development of a certain resilience or relief (of feeling cured) may play a long-term role [13].…”
Section: Annual Screening Roundcontrasting
confidence: 52%
See 3 more Smart Citations
“…Screening, in its own right, introduces the risk of negative psychosocial consequences which might be long-term. However, in the previously mentioned matched cohort study we found short-term, but no evidence supporting long-term psychosocial consequences [13]. We argue that certain long-term consequences may have been overlooked, or that the development of a certain resilience or relief (of feeling cured) may play a long-term role [13].…”
Section: Annual Screening Roundcontrasting
confidence: 52%
“…The questionnaire Consequences of Screening -Lung cancer (COS-LC) is a condition-specific questionnaire with high content validity and adequate psychometric properties developed and validated, using Item Response Theory Rasch models, to measure the psychosocial consequences of participation in lung cancer CT-screening [5,13]. COS-LC has two parts; Part 1 includes the nine scales (number of items); Anxiety (7), Behaviour (7), Sense of dejection (6), Negative impact on sleep (4), Self-blame (5), Focus on airway symptoms (2), Stigmatisation (4), Introvert (4) and Harm of smoking (2).…”
Section: The Cos-lcmentioning
confidence: 99%
See 2 more Smart Citations
“…favouring sensitivity over specificity) [e.g. 28 , 29 ]. There is currently no universally agreed concept on how to translate evidence into language, and current concepts are inconsistent and/or difficult to put into practice [ 30–32 ].…”
mentioning
confidence: 99%